Analisis Kepuasan dan Penggunaan Rekam Medis Elektronik Puskesmas Menggunakan Metode End User Computing Satisfaction dan Technology Acceptance Model - Selvia Selvia; Dolly Indra; Herdianti Darwis (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Electronic medical records (EMR) are health information systems used to improve the efficiency of patient data management and the quality of healthcare services in healthcare facilities. However, several problems have been found, such as network disruptions or errors, double workloads, and suboptimal user satisfaction levels. This study aims to analyze the level of satisfaction and use of electronic medical records and to determine the relationship between satisfaction and system use at the Tamamaung Community Health Center in Makassar City and the Community Health Center Technical Implementation Unit (UPTD) in North Kolaka Regency. The study used a quantitative approach with a cross-sectional design. Respondents in this study were 55 healthcare workers who used EMR selected using a full sampling technique (Full Sampling). Satisfaction analysis was conducted using the End User Computing Satisfaction (EUCS) and Technology Acceptance Model (TAM) methods. Analysis of the relationship between satisfaction and system use was conducted using the Spearman Rank Correlation test. The results showed that all EUCS and TAM variables were in the